Examining Trade Mechanism of International Carbon Dioxide Emission: Evidence from Major Emitter Countries - Demiral, Mehmet (International Journal of Energy Economics and Policy, 2016)
This study examines factors affecting the changes in the net exports of the carbon dioxide (CO2) emissions embodied in global trade, conducting seemingly unrelated regression-based generalized least square method. The study uses balanced panel data sets of 34 OECD and 7 major non-OECD countries in the G-20 and the period of 1996-2011. Along with various explanatory variables, we also add interaction terms between structural changes and income variables for crosschecking. Results reveal that trade openness leads to increase in emission exports, while GDP per capita has a slight negative effect. Net oil export per capita is the most important factor raising the emission export. The finding that structural changes also affect emission density affirms the importance of technological progress. Considering international trade pattern, overall results underline that nobody is responsible for global emission individually since countries emit for others. For trade mechanism of emission reduction, ‘ideal’ and ‘global’ green trade implications seem to be appropriate policy initiatives. Keywords: CO2 Emission, Emission Export, Kuznets Curve, SUR model, Structural Change. JEL Classifications: C33, F18, Q56